2007
DOI: 10.1002/ceat.200700249
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of Benzene to Maleic Anhydride in a Fluidized Bed Reactor

Abstract: In this project, the selective oxidation of benzene to maleic anhydride (MAN) was studied. Gas phase catalytic oxidation of benzene was carried out in a laboratory scale fluidized bed reactor on six different types of catalysts, which have different compositions. Effects of temperature, flow rates of benzene and air and catalyst type on the reaction selectivity were investigated at atmospheric pressure. The experiments were performed over a temperature range of 325 to 400°C, a space-time (W/F A0 ) range from 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 9 publications
0
3
0
2
Order By: Relevance
“…Industrially, the production of maleic anhydride can be divided into benzene oxidation, n -butane oxidation, and C 4 olefin oxidation according to the raw materials. , The gas-phase oxidation of furfural to maleic anhydride was popularly achieved with vanadium-based catalyst. In the 1970s, Murthy investigated the kinetics of furfural oxidation with the V 2 O 5 catalyst in the temperature range of 493–563 K , The authors found that maleic anhydride and CO 2 were generated by a parallel reaction scheme.…”
Section: Aliphatic Diacids and Anhydridementioning
confidence: 99%
“…Industrially, the production of maleic anhydride can be divided into benzene oxidation, n -butane oxidation, and C 4 olefin oxidation according to the raw materials. , The gas-phase oxidation of furfural to maleic anhydride was popularly achieved with vanadium-based catalyst. In the 1970s, Murthy investigated the kinetics of furfural oxidation with the V 2 O 5 catalyst in the temperature range of 493–563 K , The authors found that maleic anhydride and CO 2 were generated by a parallel reaction scheme.…”
Section: Aliphatic Diacids and Anhydridementioning
confidence: 99%
“…In previous research, the catalyst performance of alkali metal oxide, mainly for Cs, supported γ ‐Al 2 O 3 or ZSM‐5 was discussed for synthesis of MA via aldol condensation of MA with formaldehyde . When the V 2 O 5 ‐P 2 O 5 binary oxide as well as vanadium‐titanium binary phosphates were employed as catalysts for aldol condensation of HCHO with other substances consisting of acetone , acetic acid, and methyl acetate , excellent catalytic activity was stated and all the desired target products were obtained, which convincingly demonstrated that the acid‐base properties of these phosphates catalysts play a vital part in promoting aldol condensations .…”
Section: Introductionmentioning
confidence: 80%
“…Fluidization was established as an industrially important concept in the 1940s, during which large-scale implementation of fluid catalytic cracking was widely introduced. It soon extended its range of applications to other areas such as heat transfer, coatings, drying, combustion, gasification, chemical reactors, and adsorption. One of the advantages of fluidized beds is their ability to provide a relatively uniform bed temperature and high rates of heat transfer . Therefore, they can be used as heat exchanger apparatuses with good performance.…”
Section: Introductionmentioning
confidence: 99%